Assembly of microtubules onto kinetochores of isolated mitotic chromosomes of HeLa cells. - Telzer, B R (1975)
The kinetochores of isolated HeLa cell chromosomes attached to an electron microscope specimen grid, fixed in formaldehyde, and stained with alcoholic phosphotungstic acid are visible as dark, preferentially stained structures distinct from the chromatin with which they are associated. When unfixed chromosomes are immobilized by attachment to grids and incubated with chick brain tubulin, microtubules are observed to assemble onto the kinetochores. This demonstrates the competence of kinetochores in isolated chromosomes to act in vitro as microtubule assembly sites and suggests that they also possess this capacity in vivo. In addition, the results provide a possible means for isolating and characterizing kinetochores.